ANALISA PENCEMARAN LAUT OLEH PTT EXPLORATION AND PRODUCTION (PTTEP) AUSTRALASIA TERHADAP LAUT TIMOR INDONESIA - Paulin Yosephin Marini; Sherlly Monica Bonsapia; Johni R.V. Korwa (Jurnal PIR : Power in International Relations, 2020)
This study aims to analyze a blowout from an oil and gas leak owned by PTT Exploration and Production (PTTEP) Australasia in the Montara oil field in the Indonesian Timor Sea, and how to resolve disputes between Australia and Indonesia. A qualitative approach was used in this study, whilst the data collection technique was through library research. The theory of state responsibility, the concept of human security, and the concept of international maritime law are used to analyze disputes between Indonesia and Australia. The study found that the Montara oil spill had not only damaged the marine ecosystem but also polluted Indonesian waters. It also found that although the Australian government had formed a special commission to resolve cases and even used dispersant, it had not satisfied all parties. Several points are summarized. First, the Montara oil spill in Australia is a transnational study because the impact has crossed national borders. Secondly, UNCLOS has a weakness in the settlement of the Montara case because the Convention only provides a description related to ‘Responsibility of Each Country’ and does not specifically arrange material compensation mechanisms to countries that cause sea pollution. Third, the Montara oil spill has caused huge losses for Indonesian seaweed farmers, especially 13 districts in NTT. The recommendations are that the Indonesian government along with the Montara Victim Peoples’ Advocacy Team should continue to follow up the case of oil spills from the Montara platform and continue to fight for compensation to the Australian government and the PTTEP as the responsible party.